2009
DOI: 10.1136/ard.2008.089904
|View full text |Cite
|
Sign up to set email alerts
|

One year change of knee cartilage morphology in the first release of participants from the Osteoarthritis Initiative progression subcohort: association with sex, body mass index, symptoms and radiographic osteoarthritis status

Abstract: Objective-The Osteoarthritis Initiative (OAI) is a multicentre study targeted at identifying biomarkers for evaluating the progression and risk factors of symptomatic knee OA. Here cartilage loss using 3 Tesla (3 T) MRI is analysed over 1 year in a subset of the OAI, together with its association with various risk factors.Methods-An age-and gender-stratified subsample of the OAI progression subcohort (79 women and 77 men, mean (SD) age 60.9 (9.9) years, body mass index (BMI) 30.3 (4.7)) with both frequent symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
173
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(189 citation statements)
references
References 37 publications
13
173
1
2
Order By: Relevance
“…The primary end point (central subregions of the medial femorotibial compartment) was selected because previous results indicated that the central medial femorotibial compartment shows the greatest rate of change and sensitivity to change in cartilage thickness (20,24,26,42). In light of the previous trials showing more marked treatment effects on the lateral knee compartment as compared to the medial knee compartment (40,41), it is interesting to note that the primary end point of the present trial was not met, while dose-dependent treatment effects were found for the lateral knee compartment (lateral femorotibial compartment).…”
Section: Discussionmentioning
confidence: 99%
“…The primary end point (central subregions of the medial femorotibial compartment) was selected because previous results indicated that the central medial femorotibial compartment shows the greatest rate of change and sensitivity to change in cartilage thickness (20,24,26,42). In light of the previous trials showing more marked treatment effects on the lateral knee compartment as compared to the medial knee compartment (40,41), it is interesting to note that the primary end point of the present trial was not met, while dose-dependent treatment effects were found for the lateral knee compartment (lateral femorotibial compartment).…”
Section: Discussionmentioning
confidence: 99%
“…Metrics of cartilage morphology (volume, thickness, and others) based on MRI have been shown to be reproducible in single (1,3) and multicenter studies (4) and hold promise for evaluating the treatment response of structure/disease-modifying drugs. Several studies have reported the rate and sensitivity to change of cartilage morphology measures in participants with OA (5)(6)(7)(8)(9)(10)(11) and healthy persons (12-15) using 1.5T (1,3,16) or 3T MRI (17)(18)(19). Some of these studies have compared measures of change based on MRI to joint-space narrowing from radiographs (7,10,11,17,20).…”
mentioning
confidence: 99%
“…1). The reasons for using FA-25° 3D-DESS imaging was that the FA-25° setting is the standard imaging condition for 3D-DESS (8,13,14). The sequence parameters were similar to those used in a previous study comparing 3D-DESS and True-FISP (3).…”
Section: Imagingmentioning
confidence: 99%
“…Accurate and precise analysis of cartilage morphology in the femorotibial joint is reported to be possible with 3D-DESS at 3.0 T (8). 3D-DESS is also used for long-term cartilage evaluation by the Osteoarthritis Initiative (13). However, several reports have suggested that 3D-DESS imaging has lower cartilage-synovial fluid contrast, which makes assessment of cartilage surface lesions more difficult than other sequences (6,7,14).…”
Section: Introductionmentioning
confidence: 99%